The Reaction Order and Kinetics of Total Oxidation Reaction of M-xylene over LaMnO3 Perovskite Catalyst - Huyen, Tran Thi Thu; Hue, Dang Thi Minh; Mai, Nguyen Thi Tuyet; Luyen, Tran Thi; Lan, Nguyen Thi (VNU Journal of Science: Natural Sciences and Technology; Vol 34 No 3, 2018)
M-xylene, one of the popular toxic pollutants in exhaust gases, is emitted into the environment from factories and engines. The best solution for removing m-xylene to protect the environment is completely transforming it into CO 2 and H 2 O by catalysts. Perovskite of LaMnO 3 is one of the catalysts that was synthesized and studied for its catalytic properties in a total oxidation reaction of m-xylene in a previous report by the authors. The results showed that the LaMnO 3 perovskite had good catalytic characterizations such as large surface area and big amount of α-oxygen adsorbed on the catalyst; more specifically, LaMnO 3 perovskite exhibited a good catalytic activity in a total oxidation of m-xylene at a relatively low reaction temperature. This study determines the reaction order and kinetics of this reaction. The results show that the reaction order with respect to m-xylene was 1; to oxygen, zero, and the general order of reaction was 1. These data show that the pathway of the named reaction followed the Langmuir–Hinshelwood mechanism. Keywords Catalyst, perovskite, oxidation, m-xylene, kinetics References [1] Penã M.A and Fierro J.L.G (2001), “Chemical Stuctures and Performance of Perovskite Oxide”, Chem. Rev, 101, pp 1981-2018. [2] Seiyama T., Yamazoe N. and Eguchi K. (1985), “Characterization and Activity of some Mixed Metal Oxide Catalysts”, Ind. Eng. Chem. Prod. Res. Dev., 24, pp. 19-27. [3] Van Santen R. A., Neurock M. (2006), Molecular Heterogeneous catalysis, Wiley – VCH, pp.62-244. [4] Petrovics, Terlecki - Baricevic A., Karanovic Lj., Kirilov - Stefanov P. , Zdujic M., Dondur V., Paneva D., Mitov I., Rakic V. (2008), “LaMO3 (M = Mg, Ti, Fe) perovskite type oxides : Preparation, Characterization and Catalytic Properties in Methane deep Oxidation”, Appl. Catal. B, Env., 79, pp. 186-198. [5] Spinicci R., Tofanari A., Faticanti M., Pettiti I. and Porta P. (2001), “Hexane Total Oxidation on LaMO3 (M = Mn, Co, Fe) perovskite-type oxides”, J. Mole. Catal., 176, pp. 247-252. [6] Trần Thị Thu Huyền, Nguyễn Thị Minh Hiền, Nguyễn Hữu Phú (2006), “Study on the preparation of perovskite oxides La1-xSrxMnO3 (x = 0; 0,3; 0,5) by sol - gel citrate method and their catalytic activity for m-xylene toltal oxidation”, Hội nghị xúc tác và hấp phụ toàn quốc lần thứ IV, Tp. Hồ Chí Minh, Tr. 477-482. [7] Trần Thị Thu Huyền, Nguyễn Thị Minh Hiền, Nguyễn Hữu Phú (2009), “Nghiên cứu động học của phản ứng oxi hóa hoàn toàn m-xylen trên các xúc tác perovskit LaMnO3 và La0,7A0,3MnO3 (A = Sr, Ca, Mg)”, Tạp chí Hóa học, T.47 (6A), Tr 132-136. [8] Geoffrey C. Bond, Catherine Louis, David T. Thompson (2006), “Catalysis by Gold”, Catalytic Science Series-Vol.6.